2005
DOI: 10.1109/tpami.2005.14
|View full text |Cite
|
Sign up to set email alerts
|

Metric 3D reconstruction and texture acquisition of surfaces of revolution from a single uncalibrated view

Abstract: Image analysis and computer vision can be effectively employed to recover the three-dimensional structure of imaged objects, together with their surface properties. In this paper, we address the problem of metric reconstruction and texture acquisition from a single uncalibrated view of a surface of revolution (SOR). Geometric constraints induced in the image by the symmetry properties of the SOR structure are exploited to perform self-calibration of a natural camera, 3D metric reconstruction, and texture acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…provides four linear constraints on ω, whose coefficients can be computed from (the visible portions of) two imaged ellipses as shown in [12]. In that paper, it is demonstrated that only three out of the four constraints above are actually independent.…”
Section: Internal Parametersmentioning
confidence: 98%
See 4 more Smart Citations
“…provides four linear constraints on ω, whose coefficients can be computed from (the visible portions of) two imaged ellipses as shown in [12]. In that paper, it is demonstrated that only three out of the four constraints above are actually independent.…”
Section: Internal Parametersmentioning
confidence: 98%
“…Another desktop approach appears in [9]: by exploiting the image of two arbitrary coplanar circles, the focal length of the camera and its extrinsic parameters are obtained. Being quite common in man-made environments, surfaces of revolution (SORs) were also proposed for desktop internal calibration purposes [10] and single view metric reconstruction [11], [12]. Thanks to their symmetry properties, SORs can be conveniently used as multiple camera calibration artifacts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations